A study on the heterogeneous fleet of alternative fuel vehicles: Reducing CO2 emissions by means of biodiesel fuel. (August 2018) - Masmoudi, Mohamed Amine; Hosny, Manar; Demir, Emrah; Cheikhrouhou, Naoufel
Highlights: An extension of the heterogeneous Vehicle Routing Problem with synchronized visits is studied. New aspects such as alternative fuel vehicles, biodiesel, and carbon emissions are investigated. Three hybrid algorithms based on Artificial Bees Colony are proposed and compared. Good computational performance is achieved for the investigated problem. The benefits of a heterogeneous fleet in terms of saving consumption and emission is demonstrated. Abstract: In the context of home healthcare services, patients may need to be visited multiple times by different healthcare specialists who may use a fleet of heterogeneous vehicles. In addition, some of these visits may need to be synchronized with each other for performing a treatment at the same time. We call this problem the Heterogeneous Fleet Vehicle Routing Problem with Synchronized visits (HF-VRPS). It consists of planning a set of routes for a set of light duty vehicles running on alternative fuels. We propose three population-based hybrid Artificial Bee Colony metaheuristic algorithms for the HF-VRPS. These algorithms are tested on newly generated instances and on a set of homogeneous VRPS instances from the literature. Besides producing quality solutions, our experimental results illustrate the trade-offs between important factors, such as CO2 emissions and driver wage. The computational results also demonstrate the advantages of adopting a heterogeneous fleet rather than a homogeneous one for the use in home healthcare services.